Bildung und Arbeit als Integrationsfeld für Geflüchtete - Gibson-Kunze, Martin (HWR Berlin Forschung, 2021)
This publication presents the results of a study on the integration of refugees into education, training and work in Berlin. The research is based on qualitative interviews with refugees and representa-tives of schools, companies, civil society projects and administrative bodies. The study analyses factors that both support and hinder refugees' integration into training and work, and discusses related measures of integration management.